Reproductive responses of the endangered snail kite to variations in prey density. Issue 4 (7th April 2014) - Cattau, Christopher E.; Darby, Philip C.; Fletcher, Robert J.; Kitchens, Wiley M.
ABSTRACT Understanding how predators respond to fluctuations in prey density has important conservation and management implications, particularly for threatened and endangered specialists. However, directly linking prey densities to predator behavior and demography over broad spatial and temporal scales is rare, in part, because it can be prohibitively expensive and time‐consuming to quantify prey density over large areas. We link nesting data collected by a long‐term monitoring program for the endangered snail kite (Rostrhamus sociabilis plumbeus) with 44 density estimates of its primary prey, the Florida apple snail (Pomacea paludosa), collected by multiple, smaller‐scale studies from 2002 to 2010. We found evidence that key components of kite breeding biology—nest density and the number of young fledged per successful nest—were positively related to snail density. Although previous studies have shown that densities greater than approximately 0.1–0.2 snails/m2 may be necessary to sustain profitable foraging and that capture times for individual foraging kites begin to level off as snail densities exceed approximately 0.4 snails/m2, we found continued numerical responses in snail kite reproductive parameters at greater snail densities. At occupied sites (i.e., snail‐sampling sites in which ≥1 snail kite nest was present within a 2‐km radius during the primary sampling period: Mar–May), the average snail density was 0.45 snails/m2 (SE = 0.12, n = 17), whereas that of unoccupied sites was 0.12 snails/m2 (SE = 0.02, n = 27). Along the snail density gradient from 0.2 to 0.4 to 1.2 snails/m2, model predictions indicated that 1) the probability of site occupancy (by nesting kites) increased from 0.48 to 0.69 to 0.90, 2) local nest abundance of occupied sites increased from 4 to 7 to 16 nests, and 3) the probability of a successful nesting attempt fledging more than 1 young increased from 0.02 to 0.07 to 0.43. We found no evidence of a snail density effect on nest survival. Understanding the differential effects of snail density on various components of snail kite breeding biology is essential to the development and implementation of management tools used for snail kite conservation and Everglades restoration. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.